OPTIMIZING HUMAN POTENTIAL: INTEGRATING HUMAN RESOURCE MANAGEMENT BASED ON SPIRITUAL BEHAVIOR - Qushwa, Febriyanti Ghayatul; Hambali, Hambali; Eka Candra Dewi, Novela; Hakim, Lukman; Maulina Rifkiyatul Islami, Ica (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Human potential in human resource management is divided into four parts, first emotional potential, second physical potential, third intellectual potential, fourth spiritual potential. The existence of human potential by integrating human resource management based on spiritual behavior. This research aims to build human ethics and morality in interacting, build human potential in developing skills, balance welfare at work and create an environment that is in accordance with inspiration or a desired goal. . By using qualitative research methods, literature study or library research. The results of this research show that based on a study of several scientific works that have been presented, it can be concluded that optimizing human potential by integrating spiritual behaviorbased human resource management can be done in three ways, namely by paying attention to several things including, the importance of values and ethics, creating prosperity. in individuals or groups, making leadership spiritually based. These three things refer to an approach to human resource management that emphasizes the importance of spiritual values, ethics and morality in the work environment. This approach can improve employee welfare, productivity and organizational sustainability